Pelvimetry in nulliparous and primiparous women using 3 Tesla magnetic resonance imaging - Hampel, Franziska; Sohn, Christof; Schlehe, Bettina; Brocker, Kerstin A. (Neurourology and urodynamics, 2018)
Aims To perform pelvimetry in nulliparous and primiparous women using 3 Tesla magnetic resonance imaging (3T MRI). Methods Twenty-five nulliparous volunteers and 25 primiparous women underwent pelvic 3T MRI within one week after vaginal childbirth in a prospective clinical single-center trial. The pelvimetric parameters interspinous distance (ISD), intertuberous distance (ITD), sagittal outlet (SO), obstetric conjugate (OC), and coccygeal curved length (CCL) were adapted from anthropometric measurements as well as from sonographic and computed tomography-based pelvimetry performed on high-resolution T2-weighted images. We compared the results of the two study groups to one another, recent literature and postpartum-diagnosed levator ani muscle (LAM) injuries. Results The mean values for primipara/nullipara were ISD 107 ± 8.3/105 ± 8.4 mm, ITD 119.8 ± 10.2/118.4 ± 13.1 mm, OC 129.4 ± 10/130.8 ± 6.9 mm, SO 114.3 ± 7.8/112.5 ± 8.9 mm, and CCL 37.3 ± 7.4/39 ± 8 mm. Significant differences (P < 0.05) were found between the results for OC, SO, and CCL (primipara) and ISD, ITD and OC (nullipara) and the values in the literature. No significant difference in pelvimetric values was found between the groups. A significant correlation was found between the pelvimetric parameters and five types of LAM injuries. Conclusions Two-dimensional 3T MRI combines high-resolution images with objective pelvimetric measurements applicable in a postpartum setting. Our results provide a good foundation for further MRI-based studies evaluating the bony pelvis and its relation to LAM injuries during vaginal childbirth.
Gesehen am 21.08.2019